2015
DOI: 10.1111/ocr.12112
|View full text |Cite
|
Sign up to set email alerts
|

The Cleft Care UK study. Part 4: perceptual speech outcomes

Abstract: Structured AbstractObjectivesTo describe the perceptual speech outcomes from the Cleft Care UK (CCUK) study and compare them to the 1998 Clinical Standards Advisory Group (CSAG) audit.Setting and sample populationA cross-sectional study of 248 children born with complete unilateral cleft lip and palate, between 1 April 2005 and 31 March 2007 who underwent speech assessment.Materials and methodsCentre-based specialist speech and language therapists (SLT) took speech audio–video recordings according to nationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 48 publications
11
101
1
4
Order By: Relevance
“…The Cleft Care UK (CCUK) study is a United Kingdom (UK)‐wide cross‐sectional study of 5‐year‐old children born with complete unilateral cleft lip and palate (cUCLP) . Recently reported findings from CCUK showed that outcomes in speech and dentoalveolar and facial form following treatment of cUCLP in the UK have improved since services were reorganized to a more centralized model of care . This reorganization of cleft services in the UK achieved a more multidisciplinary and audited service with designated cleft surgeons performing at least ~40 primary cleft repair operations (including all cleft types) per year .…”
Section: Introductionmentioning
confidence: 99%
“…The Cleft Care UK (CCUK) study is a United Kingdom (UK)‐wide cross‐sectional study of 5‐year‐old children born with complete unilateral cleft lip and palate (cUCLP) . Recently reported findings from CCUK showed that outcomes in speech and dentoalveolar and facial form following treatment of cUCLP in the UK have improved since services were reorganized to a more centralized model of care . This reorganization of cleft services in the UK achieved a more multidisciplinary and audited service with designated cleft surgeons performing at least ~40 primary cleft repair operations (including all cleft types) per year .…”
Section: Introductionmentioning
confidence: 99%
“…However, children born with cleft have a much higher rate of persistent speech problems with approximately 50% showing difficulties with making themselves understood at age 5 (Sell et al . ). Additional risk factors for suboptimal speech and language outcomes in this population include the size of the cleft and the timing and methods of surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
“…The primary driver of the initial collection of the data in the CC-SL study is the imperative to identify the precursors and risk factors associated with poor speech outcome at age 3 years and of later persistent speech disorder, given that children born with cleft palate are a high-risk group for both outcomes (Sell et al 2015). Whilst the type and degree of cleft are undoubtedly important in speech outcome, other factors related to the child's physical and psychosocial development as well as environmental and genetic factors are also thought to play a part.…”
Section: The Cleft Collective Speech and Language (Cc-sl) Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Children born with a cleft, particularly involving the palate, are at higher risk of poor speech outcomes at three-years-old (i.e. before entering school) and persistent speech disorder 24 , both of which are strongly associated with lower educational attainment 41 . Teasing and bullying by peers is common in children born with clefts 22 , which can affect psychological wellbeing, enjoyment of school and attainment 42 .…”
Section: Comparison To Previous Evidencementioning
confidence: 99%